INTIMATE (Integration of Ice-core, Marine and Terrestrial Records) 20 Years on: Retrospect and Prospect. (2nd April 2016) - Walker, Mike
Abstract: The INTIMATE (Integration of ice-core, marine and terrestrial records) project, the successor to the North Atlantic Seaboard Programme of International Geological Correlation Programme (IGCP-253) 'Termination of the Pleistocene', began in 1995 with the aim of integrating proxy climate records from around the North Atlantic during the Last Termination (18–8 ka BP). The INTIMATE remit has since expanded geographically to include the entire Atlantic basin and Australasia, while an extended temporal framework now covers the early Holocene and the Last Glacial cycle. This short paper outlines the principal achievements of the INTIMATE research community, which include the development of an event stratigraphy for the North Atlantic region; the establishment of protocols for ice–land–ocean correlation; important contributions to geochronology, most notably to tephrochronology, and to palaeoenvironmental and palaeoclimatic reconstructions; and the designation of the Greenland ice-core record as the global stratotype for the Pleistocene–Holocene boundary. Future directions of the INTIMATE programme are also briefly considered.